Formulation, Stability Test and Antibacterial Activity of Banana Leaf Extract Liquid Soap (Musa sp.) against the Growth of Escherichia coli - Wahyuningsih, Erpika Ambar; Khumaira, Annisa (BIOEDUKASI, 2024)
Liquid soap is an important component in maintaining skin cleanliness. Good liquid soap is soap that contains natural antioxidants because it can protect the body from free radicals and prevent cell damage and is also antibacterial because it can prevent and kill pathogens. One source of easily available phytochemical compounds with antioxidant and antibacterial activity is banana leaves (Musa sp.). The aim of this research was to formulate physically and chemically stable banana leaf extract liquid soap and test the antibacterial effectiveness of banana leaf extract liquid soap with formulations of 0%, 1%, 3%, 5% and 7% against the growth of Escherichia coli. This research was carried out using Completely Randomized Design which included making extracts, phytochemical screening tests, organoleptic tests, hedonic tests, pH tests, homogeneity tests, foam stability tests, and antibacterial tests on Escherichia coli using the diffusion method (paper disc). Then statistical analysis of variance (ANOVA) was carried out to determine the differences in the five formulas. Integrating banana leaf phytochemical compounds into soap formulas produces products that are antioxidant and antibacterial. The best formula is at an extract concentration of 7% because it provides optimal antibacterial test results and meets SNI standards for foam stability.